Continental subductions and Tibetan plateau growth - Guillot, Stephane; Replumaz, Anne (Journal of Nepal Geological Society, 2013)
How and when the Tibetan plateau developed has long been a puzzling question with implications for the current understanding of the behaviour of the continental lithosphere in convergent zones. We present and discuss recent data acquired in geology and geophysics and through igneous and metamorphic petrology and palaeo-altitude estimates. This research indicates that Tibet initiated from the accretion of the Gondwana continental blocks to the southern Asian margin during the Palaeozoic and Mesozoic eras. These successive accretions have potentially favoured the creation of local landforms, particularly in southern Tibet, no evidence exists in favour of the existence of a proto-Tibetan plateau prior to the Cenozoic. By the time the India-Asian collision began it was cold enough to transfer stress but that does not mean there was not a proto-plateau prior to collision. Depending on the types of Paleozoic and Mesozoic collisions, the sutures terranes could be cool enough to transfer stress, especially in the upper crust. However, these successive accretions associated with subductions have metasomatized the Tibetan lithospheric mantle and largely explain the potassium- and sodium-rich Cenozoic magmatism. Another consequence of this contamination by fluids is the softening of the Tibetan lithosphere, which favoured intracontinental subductions. The timing and the geochemical signatures of the magmatism and the palaeo-altitudes suggest the early growth of the Tibetan plateau. By Eocene time, the southern plateau and the northern portion of Himalaya were at an altitude of approximately 4000 metres, while the central and northern Tibetan plateau was at altitudes of approximately 2000 to 3000 meters at the Eocene-Oligocene transition. From all of these data, we propose a model of the formation of the Tibetan plateau coupled with the formation of Himalaya, which accounts for more than 2500 km of convergence accommodated by the deformation of the continental lithosphere.